Age‐related changes in skeletal muscle mass among community‐dwelling Japanese: A 12‐year longitudinal study. (February 2014) - Shimokata, Hiroshi; Ando, Fujiko; Yuki, Atsumu; Otsuka, Rei
Abstract : Aim: The present study aimed to evaluate age‐related changes in skeletal muscle mass among community‐dwelling middle‐aged and elderly Japanese. Methods: This 12‐year longitudinal study of a community‐dwelling population in Japan included 15 948 examinations of 1962 men and 1990 women. We assessed appendicular muscle mass (AMM) using dual X‐ray absorptiometry and calculated the skeletal muscle index (SMI) using the AMM divided by height squared (kg/m 2 ). Low muscle mass was defined as muscle mass minus two standard deviations below the mean for young healthy adults. Leg extension power (watts) was measured as an index of muscle function. Longitudinal data of skeletal muscle mass were analyzed using a general linear mixed‐effect model. Results: The prevalence of low muscle mass at the first wave of examinations was 27.1% in men and 16.4% in women. Longitudinal analysis showed that skeletal muscle mass decreased with aging during the 12‐year study period except in middle‐aged men, and to a greater extent in elderly men ( P for trend, <0.001). Skeletal muscle mass decreased slightly, but significantly, in women. Although a cross‐sectional analysis showed that SMI did not differ with age in women, leg extension power per leg muscle mass and grip strength per arm muscle mass as indices of muscle quality were significantly lower in older women ( P for trend, <0.001 for both). Conclusion: Age‐related decreases in muscle mass were trivial, especially in women, but the quality of muscle decreased with aging in both sexes.Geriatr Gerontol Int 2014; 14 (Suppl. 1): 85–92.